Establishing a Set of Professional Standards for Principals in Taiwan - Wang, Ru-Jer; Huang, Yueh-Chun (Advances in Social Sciences Research Journal, 2020)
The purpose of this study is to formulate a set of professional standards for principals in Taiwan. The research methodology employed was fuzzy Delphi. An initial set of 52 standards was formulated and then revised by a panel of 20 experts. The main findings of this study are: the standards are divided into four dimensions: professional knowledge (14 standards), value and vision (11 standards), professional attitude (14 standards), and professional behavior and performance (13 standards). The standards established by this study can be a useful tool for the recruitment of future school principals and a useful instrument for the evaluation of current school principals due to the fact that Taiwan currently lacks a standardized set of professional standards for school principals. This study provided a good example of formulating a set of professional standards for school principals suited to a certain country for having taken its specific local context into account and having learned from the sets of standards in use elsewhere as well.